La desnutrición infantil y su relación con el desarrollo psicomotor en los niños de 0 a 3 años del centro infantil el pequeño Emanuel de la parroquia de Lican, provincia de Chimborazo, periodo 2016-2017 - Pazos Guevara, Verónica Patricia (2017)
This research was conducted in order to determine whether the exactness for the teaching are related or influence on language and literature learning. Firstly the problem statement and specific objectives were done. Then the scientific, philosophical, axiological, educational, and legal foundation was made. Additionally theoretical foundations where able to clear the two study variables, these pressures for teaching and learning language and literature that seek to consolidate the development of critical thinking in greater depth and systematic way in relation to which it has worked so far and the purpose is to develop student thinking a critical way, systematic and coherent. It states that this is a job, which must be developed with the child, it is essential the guiding role and accompanying teachers; and participation and actively motivated as a student. Also through research, it was determined that the learning of language and literature is an essential part of teaching children, where teachers should give greater interest and especially in children with complications. Learning activities to strengthen language and literature was proposed, and then the definition of terms and operationalization was made. In the methodological framework it worked with the inductive, deductive, analytical, field and descriptive method, when the study population was taken it proceeded to the tabulation of data through graphical representation where it was analyzed and interpreted the results and finally the conclusions and recommendations were developed based on the specific objectives.